Design, synthesis, and photoelectric properties of V-shaped organic fluorescent compounds with a 1, 3, 4-oxadiazole moiety. Issue 1 (January 2019) - Hou, Rui-Bin; Su, Ji-Ying; Zhang, Ling-Ling; Li, Dong-Feng; Xia, Yan
A series of symmetric, silicon-linked organic fluorescent compounds with two electron-deficient 1, 3, 4-oxadiazole units were synthesized and characterized. The compounds possessed a V-shaped structure with a silicon atom, which weakened π–π stacking, promoting aggregation-induced emission. The compounds were fluorescent in both solution and solid-state thin films. The efficient fluorescent behavior of the materials was confirmed through optical and electrochemical measurements. The compounds displayed excellent thermal stability, with decomposition temperatures exceeding 400 °C. Amorphous films of the compounds possessed high morphological stability. These results indicate that the compounds may be promising emissive and electron-transporting materials.